The Effects of Concentration, Temperature and Solvent Composition on Partial Molar Volumes of Cetyltrimethylammonium Bromide in Methanol-Water mixed Solvent Media - Shah, Sujit Kumar; Bhattarai, Ajaya; Shrivastav, Ghanashyam; Chatterjee, Sujeet Kumar (Journal of Nepal Chemical Society, 2009)
The author Ajay Bhattarai was changed to Ajaya Bhattarai and the author Kumar Chatterjee was changed to Sujeet Kumar Chatterjee Precise measurements on the density of cetyltrimethylammonium bromide solutions in pure water and in methanol(1) + water (2) mixed solvent media containing 0.10, 0.20 and 0.30 volume fractions of methanol at 308.15, 318.15 and 323.15 K are carried out to calculate the partial molar volumes. The concentrations are varied from 0.3 - 1.0 x 10-1 mol.l-1. The results showed almost constant on the partial molar volumes with increasing surfactant concentration. Also, the partial molar volumes are found to increase with increasing temperature over the entire concentration range investigated in a given mixed solvent medium and these values are found to decrease with increasing methanol content in the solvent composition. Keywords: Mixed solvent; Cetyltrimethylammonium bromide; Surfactan; Partial molar DOI: 10.3126/jncs.v24i0.2383 Journal of Nepal Chemical Society, Vol. 24, 2009 Page: 24-30